Pengaruh Promosi dan Pelayanan terhadap Minat Nasabah Gadai Emas (Studi pada Bank Syariah Indonesia KCP Muara Bulian) - Chasna, Arfial; Usdeldi, Usdeldi; Syahrizal, Ahmad (ARZUSIN, 2024)
This research aims to determine the influence of Promotion and Service on Gold Pawning Customer Interest at Bank Syariah Indonesia KCP Muara Bulian. This research used a quantitative approach which was carried out by distributing questionnaires to 73 respondents. The data analysis methods used in this research are instrument tests (validity and reliability tests), classical assumption tests (normality, multicollinearity and heteroscedastic tests) and multiple linear regression analysis and statistical tests (t test, F test and coefficient of determination R2 ). The results of this research show that promotion has a positive and significant effect on customer interest, which is known by the t test with a significant value of 0.001 < 0.05 and a value of tcount > ttable, namely 3.837 > 1.66660. Service has a positive and significant effect on customer interest as proven by The significant value is 0.001 < 0.05 and the value and value of tcount > ttable is 5.112 > 1.66660. Simultaneously promotion and service have a positive and significant effect on customer interest in Bank Syariah Indonesia KCP Muara Bulian as seen from fcount > ftable or 41.587 > 3.13 and the resulting significance value is 0.001 < 0.005. The determinant coefficient value is 0.543 or 54.3% and the remaining 0.457 or 45.7 can be explained by other variables outside this research.